2022
DOI: 10.3390/dairy3030038
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variations of Milk Composition of Sarda and Saanen Dairy Goats

Abstract: Traditionally, in Mediterranean areas the goat population was composed of autochthonous breeds with strong milk production seasonality. In the last decades, high productive alpine breeds were introduced together with more widespread out-of-season milk production practices. This study is a large-scale survey on the seasonal variations of the main compositional characteristics of goat milk obtained from Sarda and Saanen breeds reared on the Mediterranean island of Sardinia (Italy). Analysis of data indicated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
4
1
1
Order By: Relevance
“…Milk from Tinerfeña goats had the lowest protein and dry matter content, while the Majorera breed had the lowest fat percentage. Season-dependent differences in the chemical and physical composition of milk from the autochthonous Sarda breed and imported Saanen goats bred in Sardinia were presented by Scano et al (2022). The results showed that the milk of the Sarda breed was richer in protein, fat and lactose and had a lower urea content than the milk of Saanen goats.…”
Section: Discussion Milk Parametersmentioning
confidence: 99%
“…Milk from Tinerfeña goats had the lowest protein and dry matter content, while the Majorera breed had the lowest fat percentage. Season-dependent differences in the chemical and physical composition of milk from the autochthonous Sarda breed and imported Saanen goats bred in Sardinia were presented by Scano et al (2022). The results showed that the milk of the Sarda breed was richer in protein, fat and lactose and had a lower urea content than the milk of Saanen goats.…”
Section: Discussion Milk Parametersmentioning
confidence: 99%
“…Botton et al (2019) and Simioni et al (2014) from Brazil reported that the APC level was shown to be higher during the winter season compared to other seasons [47,48]. In another study by Scano and Caboni (2022) (Italy), APC in raw milk was higher during winter than in the spring and summer seasons [49]. Margatho et al (2018) from Portugal found that APC count was higher in the wet season-winter (2.65) and autumn (2.62)-compared to summer (2.56) and spring (2.50) [50].…”
Section: Total Bacterial Count (Apc) In Raw Milk Pasteurized Milk And...mentioning
confidence: 93%
“…Başka bir çalışmada, Erduran & Dag (2021), Saanen x Kıl keçisi melezlerinde hem mevsimin hem de süt veriminden kaynaklanan değişimin benzer şekilde olduğu görülmüştür. Scano & Caboni (2022) tarafından Saanen ve Sarda keçilerinde 4 yıl süreyle yürütülen çalışmada sütün yağ, protein ve yağ/protein oranlarının yaz aylarında azaldığı, sonbahar aylarında ise arttığı bildirilmiştir. Ayrıca bu çalışmada, sütün temel bileşenlerinden olan laktoz ve proteinin bunlara bağlı olarak da yoğunlukta meydana gelen değişimin sütteki YKM miktarını etkilediği bununla birlikte laktasyon döneminin de etkili olduğu saptanmıştır.…”
Section: Süt Bileşenleriunclassified